Effectiveness of mental health interventions for older adults in South Asia: A scoping review. - Hoimonty Mazumder; Farah Faizah; Easter Protiva Gain; Irfath Sharmin Eva; Kaniz Ferdouse Mou; Nobonita Saha; Farzana Rahman; Jyoti Das; A M Khairul Islam; Fazilatun Nesa; M Mahbub Hossain (PLoS ONE)
Objective Mental health problems among older adults are becoming a growing public health concern in South Asia due to continued changes in population dynamics caused by declining fertility rates and increasing life expectancy. This scoping review aimed to explore and summarize evidence about mental health interventions and their impacts on geriatric mental health and highlight gaps and areas for future research. Methods We searched six electronic databases and additional sources for experimental/non-experimental studies evaluating the effectiveness of geriatric mental health interventions in eight countries in the South Asia region from the date of inception of each database up to August 5, 2022. Following the preliminary screening, we extracted data from the eligible articles using a Microsoft Excel data extraction worksheet. We followed Joanna Briggs Institute (JBI) guidelines for this scoping review and reported evidence adhering to the Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for Scoping Reviews (PRISMA-ScR) checklist. Results From a total of 3432 potential articles retrieved, 19 were included in this review following pre-determined eligibility criteria. Across studies, mental health interventions can be broadly categorized into the following types- 1) traditional Yoga, Tai chi, or other meditative movements; 2) behavioral, occupational, or learning-based interventions; 3) tech-based interventions; 4) music therapy; and 5) new healthcare model. The evidence was predominantly based on India (n = 16), whereas three articles were identified from Pakistan. No article was found from six other South Asian countries. Depression and anxiety were the most frequent mental health outcomes, followed by quality of life, cognitive function, self-esteem, physical performance, and many more. Conclusion Although limited, this review found various interventions that have varying effects on different geriatric mental health outcomes. A handful of evidence on mental health intervention in South Asia indicates a lack of acknowledgment that may develop a serious paucity of geriatric mental health practice. Therefore, future researchers are encouraged to conduct empirical studies to understand disease burden, including associated factors of geriatric mental health, which may help to construct contextually appropriate mental health interventions in this region.